EFEKTIVITAS PENDIDIKAN KESEHATAN SADARI MELALUI ZOOM TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRI PADA MASA PANDEMI - Herniyatun, Herniyatun (Jurnal Ilmiah Kesehatan Keperawatan, 2021)
Background: Breast cancer is a scary scourge for every woman. The cause of the high number of breast cancer due to lack of knowledge early on related to early detection of breast cancer through breast self examination. The Covid- 19 pandemic has affected almost all sectors of life. Breast self examination health education intervention through Zoom becomes an alternative that can be done to provide health education in pandemic era.Objective: Knowing the effectiveness of providing breast self examination health education through Zoom on the level of knowledge of teenage girls in Kedungjati village.Metods: This type of research an experimental quasi study with pre-test and post-test with desaign group control. The study sampled 80 respondents, who were taken using purposive sampling. The data analysis used statistical tests of Wilcoxon and Mann Whitney. Using a questionnaire with 13 questions.Results: Wilcoxon tests found p=0.003 (p<0.05) in the leaflet group and p=0.000 (p<0.05) in the Zoom group. While the effectiveness difference test using mann whitney obtained a result of p = 0.000 (p<0.05).Conclusion: Breast self examination health education through Zoom is effective at increasing the level of knowledge in teenage girls.Recommendation: Health agencies are expected to cooperate with schools or village communities to provide health education at regular intervals.